Whole-genome resequencing reveals genetic diversity and selection characteristics of dairy goat - Xiong, Jinke; Bao, Jingjing; Hu, Wenping; Shang, Mingyu; Zhang, Li (Frontiers in Genetics, 2023)
The dairy goat is one of the earliest dairy livestock species to have been domesticated, and plays an important role in the economic development of developing countries. With the development of agricultural civilization, dairy goat have become widely distributed across the world. However, few studies have been conducted on the specific characteristics of dairy goats. In this study, we collected the whole-genome data of 89 goat individuals by sequencing 48 goats and employing 41 publicly available goats. Our whole-genome data was comprised of five dairy breeds (Saanen, Nubian, Alpine, Toggenburg, and Guanzhong dairy goat; n = 24, 15, 11, 6, 6), and three non-dairy breeds (Guishan goat, Longlin goat, Yunshang Black goat; n =6, 15, 6). The eight goat breeds could be divided into three subgroups of European, African, and Chinese indigenous goat populations. Through the analysis of population genetic diversity, we found that Australian Nubian, Toggenburg, and Australian Alpine had the highest linkage disequilibrium, the lowest of nucleotide diversity, and a higher inbreeding coefficient, indicating that they were strongly artificially selected. In addition, through selection signal and gene enrichment analysis, we identified several candidate genes related to the specificity of dairy goat, particularly genes associated with milk production traits (GHR, DGAT2, ELF5, GLYCAM1, ACSBG2, ACSS2), reproduction traits (TSHR, TSHB, PTGS2, ESR2), immunity traits (JAK1, POU2F2, LRRC66). Our results not only provide insights into the evolutionary history and breed characteristics of dairy goats, but also provide valuable information for the implementation and improvement of dairy goat cross breeding program.